2018
DOI: 10.1101/468421
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

WUSCHEL acts as a rheostat on the auxin pathway to maintain apical stem cells inArabidopsis

Abstract: To maintain the balance between long-term stem cell self-renewal and differentiation, dynamic signals need to be translated into spatially precise and temporally stable gene expression states. In the apical plant stem cell system, local accumulation of the small, highly mobile phytohormone auxin triggers differentiation while at the same time, pluripotent stem cells are maintained throughout the entire life-cycle. We find that stem cells are resistant to auxin mediated differentiation, but require low levels o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The WOX genes are indeed both up- and down-stream of the auxin and cytokinine pathways in meristem development [63]. For instance, WUS protects apical stem cells from differentiation by restricting the auxin signaling pathway via regulation of histone de-acetylation [124]. In addition, WUS directly represses the type-A ARR5 , ARR6 , ARR7 , and ARR15 genes, which function in the negative feedback loop of cytokinin signaling [125].…”
Section: Discussionmentioning
confidence: 99%
“…The WOX genes are indeed both up- and down-stream of the auxin and cytokinine pathways in meristem development [63]. For instance, WUS protects apical stem cells from differentiation by restricting the auxin signaling pathway via regulation of histone de-acetylation [124]. In addition, WUS directly represses the type-A ARR5 , ARR6 , ARR7 , and ARR15 genes, which function in the negative feedback loop of cytokinin signaling [125].…”
Section: Discussionmentioning
confidence: 99%
“…However, this viewpoint has been challenged by recent studies involving high-resolution imaging of the localization of PIN1 and the auxin biosensor DII-Venus. According to these studies, the central zone of the SAM generally contains high levels of auxin, although low levels of auxin signaling occur in this region [19,20]. The central high-auxin zone forms periodical protrusions that coincide with incipient primordia, which is specified by the duration of cell exposure to auxin.…”
Section: The Role Of Auxin In Regulating Leaf Initiationmentioning
confidence: 99%
“…In addition, prolonged co-treatment of auxin perception antagonist auxinole, and auxin biosynthesis inhibitors yucasin and kyn led to expansion and restriction of KAN1 and REV expression toward the SAM center, respectively [43]. It remains to be tested whether auxin directly regulates the expression of REV and/or KAN1 , or auxin affects the SAM homeostasis, as recently suggested [19], and indirectly affects the prepattern.…”
Section: The Role Of Auxin In Regulating Leaf Shapementioning
confidence: 99%
“…Also, it has been reported that in SAM, wus protein can act as a transcriptional activator or repressor of auxin signaling component on the regulatory environment. In Arabidopsis, wus gene seems to act both upstream and downstream of the key ARF transcription factors due to reduced auxin under stress (Ma et al, 2018). Functional studies in NAM/NAC have revealed that many of the NAC TFs regulate immune responses in plants.…”
Section: Analysis Of Co-expressed Genes In Gene Networkmentioning
confidence: 99%